VD_FINDINFO HC / 2015 / 320 vom 18. März 2015 - VD Tribunal cantonal (2015)
ACTE DE RECOURS, DÉCISION D'IRRECEVABILITÉ, DÉLAI DE RECOURS, AVANCE DE FRAIS | 319 let. b ch. 1 CPC (CH), 321 al. 2 CPC (CH)